Effect of total solids standardization using different methods on mineral content of yoghurt - Firuze Ergin; Murat Kılıç; Serpil Kılıç; Ahmet Küçükçetin (Mljekarstvo)
Yoghurt is a good dietary source of macro and micro minerals. However, the mineral content of yoghurt can vary according to the technological processing used in its manufacture. In this context, the aim of this study was to compare some macro (Ca, K and Mg) and micro (As, Cd, Co, Fe, Mn, Ni, Pb, Se, V and Zn) mineral contents of total solids-standardized yoghurts with four different methods by following: (1) Addition of skim milk powder to milk, (2) Concentration of yoghurt milk by vacuum evaporation, (3) Concentration of yoghurt curd in a cloth bag and (4) Concentration of yoghurt curd by mechanical centrifugation. The highest content of the macro minerals was in the yoghurt produced with method 1, while the highest content of most of the micro minerals was in the yoghurt produced with method 4. The results of this study showed that the mineral content of yoghurt could be modified by the method used in the manufacture of yoghurt to standardize total solids content.